DISEÑO DE UNA LÍNEA DE PRODUCCIÓN DE ETANOL A BASE DE RESIDUOS DE LA CAÑA DE AZÚCAR - Malavé Macías, María Verónica (2023)
In the 19th century, the first oil industry was born in the United States based on the discovery of the first well and this was commercialized worldwide, the technology created various production lines from it such as fuel, kerosene. The current problem about the decrease in fossil reserves has generated the search for other alternatives, where they do not contain a high polluting index in their fuels, such as the use of ethanol, Certainly, in several countries they have produced ethanol with the use of corn. This has reduced pollution and dependence on oil with high prices in countries that did not produce it, but thanks to other sources it has declined and in turn has helped the environment.